Monetary Policy, Firm Size And Equity Returns In An Emerging Market: Panel Evidence Of Malaysia - Abdul Karim, Zulkefly; Zaidi, Mohd Azlan Shah (Asian Academy of Management (AAM), 2015)
The present study provides new empirical evidence on the effects of monetary policy shocks (domestic and international monetary policy) on equity returns in an emerging economy (i.e., Malaysia) for 1990–2008 using firm-level data. Using an augmented Fama-French (1992, 1996) multifactor model, empirical results based on system GMM estimations and a sample of 449 firms shows that firms' stock returns responded negatively to monetary policy shocks. Moreover, the effect of domestic monetary policy shocks also have differential effects, with a statistically significant impact on small firms' equity returns but not on large firms' stock returns. The effect of international monetary policy upon equity returns is also heterogeneous by firm size; significant effects were observed for the equity returns of large firms but not for a case of small firms.